Pregnancy-Specific β1-Glycoproteins: Combined Biomarker Roles, Structure/Function Relationships and Implications for Drug Design - T. Moldogazieva, Nurbubu; M. Mokhosoev, Innokenty; A. Terentiev, Alexander (Current Medicinal Chemistry, 2017)
Background: Pregnancy specific β1-glycoproteins (PSGs) have long been recognized as trophoblast quality and embryo viability markers. However, biological roles of PSGs remain obscure, and structure/function relationships to other feto-placental proteins as well as implications for drug design have not been reviewed. This review summarizes and discusses advances in 45-year studies of PSGs with focus on the latest achievements and the challenges for future investigations. Methods: Literature search was performed to review the majority of recent PSG studies with emphasis on usage of high-throughput integrated proteomic profiling technologies, systems biology and bioinformatics approaches that enhance novel biomarker and drug target discovery as well as protein structure/activity analysis. Results: Clinical significance and screening performance improved when PSG measurements were combined with those of other placenta-derived proteins: hCG, hPL, PAPP-A, and proMBP. Nevertheless, analysis of protein co-expression and co-localization data and the involvement of PSGs in protein interaction networks are being introduced to discover novel, specific and high-sensitive, gestational/cancer biomarkers. Despite biological roles of PSGs are not fully understood, there are evidences of that they exhibit immunomodulatory, antiinflammatory and proangiogenic effects. Investigation of structure/function relationships showed that PSGs may function in cooperative/coordinated manner with numerous regulatory proteins including alpha-fetoprotein and transforming growth factors-β; this is provided by the presence of conserved short linear motifs (SLiMs) such as RGD, PXXP and AFP14-20-like (YXCX) ones. Conclusion: PSG-derived peptides may be used as a rationale to design novel drugs that mimic SLiMs involved in protein-protein interactions to inhibit domain-motif binding and to block cell signaling, and/or exert immunomodulatory, anti-inflammatory and proangiogenic effects.
Keywords: novel drug design